Perceptions towards Engagement: The Case of Thai English Majors in an International Higher Education Environment - Loo, Daron Benjamin; Keough, Wendy; Sundaresan, Anita; Thomas, Darrin (LEARN Journal: Language Education and Acquisition Research Network, 2018)
This study examines Thai English majors’ perception towards engagement. The aim of this study is to be better informed of the English language learning experience of students in an international environment where English is used as a foreign language. A mixed methods approach was employed. A modified version of the National Survey of Student Engagement (NSSE) was used to collect quantitative data, while qualitative data was collected through a focus group interview. Correlation scores and one-way Anova were calculated to examine the survey data. Results indicated that almost all the categories of engagement were significantly correlated, except for the correlation between supportive learning environment and faculty interaction. The one-way Anova test, on the other hand, revealed that students’ year of study had a significant effect on at least three components of engagement. The quantitative results were further informed by data collected from a focus group interview. From the interview, students were able to describe the classroom atmosphere, teachers’ pedagogical strategies, as well as challenges they faced in their studies. From the findings, it was evident that the Thai students were open to different pedagogical approaches, and that they were not culturally constrained. This may be the hallmark of international education, wherein students take on a contextualized approach to learning, aside from being in a context where a foreign language is used.